Using real-time traffic pattern detection for dynamic cache size tuning in information retrieval - Wu, R.; Wong, A.K.Y.; Dillon, Tharam S. (IEEE, 2005)
The novel RTPD/MACSC model proposed in this paper tunes the cache size adoptively on the fly. It combines the extant MACSC (model for adaptive cache size control) and the novel RTPD (real-time traffic pattern detection) capability. Similar to its MACSC predecessor, the new RTPD/MACSC tuner maintains the given cache hit ratio consistently and persistently. It, however, differs from its predecessor because it adapts itself to compensate for the ill effects on the cache hit ratio by the Internet traffic, which embeds various patterns over time. The automatic adaptation (self-tuning) capability in response to traffic pattern changes detected by the RTPD is called self-reconfiguration in the RTPD/MACSC context.